SUBDUCTION-RELATED DIAMONDS? - THE EVIDENCE FOR A MANTLE-DERIVED ORIGIN FROM COUPLED δ13C - δ15N DETERMINATIONS - Cartigny P.; Girard M.; Javoy M.; Harris J.W.; Phillips D. (My University, 1998)
For the first time, δ13C–δ15N of more than 150 diamonds of known paragenesis, originating from different localities are reported. These coupled δ13C–δ15N determinations argue against a direct formation from subducted biogenic carbon for most of these diamonds. Our data confirm the apparent isotopic disequilibrium of nitrogen between the internal (mantle) and external (atmosphere+crust) reservoirs of the Earth, and thus support the heterogeneous accretion model of the Earth inferred from earlier fibrous diamond studies. We suggest that non-fibrous diamonds have recorded the evolution of the nitrogen isotopic composition starting from a δ15N-value lower than −25‰ to the present δ15N-value around −5‰. This isotopic composition change of man